Effect of Cash Flow and Working Capital on Liquidity: The Mediation Role of Profitability - Jannati Tangngisalu; Abdul Halik; Marwan Marwan; Edy Jumady (Atestasi : Jurnal Ilmiah Akuntansi, 2022)
This study examines the effect of cash flow and working capital on liquidity with profitability as an intervening variable in the retail industry listed on the Indonesia Stock Exchange (IDX) in 2019-2021. The population in this study are retail companies listed on the Indonesia Stock Exchange (IDX) in the observation period from 2019 to 2021, with as many as 27 retail companies. The sample selection used the purposive sampling method and obtained a total sample of 21 companies that meet the criteria. The statistical method used to test the hypothesis is to use panel data regression with the help of Eviews software. The results of this study indicate that cash flow and working capital have a positive and significant effect on liquidity. Cash flow and working capital have a positive and significant impact on profitability. Profitability has a positive and significant effect on liquidity. Cash flow has a positive but not significant impact on liquidity through profitability, and working capital has a positive and significant effect on liquidity through profitability.